Teachers’ conceptions about assessment: on guidelines, discourse, and practice - Pizarro Gamero, Edris Alexis; Gómez Muskus, Shirlena Sofía (Universidad Pedagógica y Tecnológica de Colombia, 2019)
This article presents the results of a case study carried out with high school teachers of different areas of knowledge, which aims to analyze the transformation of conceptions about learning assessment based on guidelines laid down in Decree 1290 of 2009. For this purpose, an interpretation of coherence was made between explicit conceptions and that established in Institutional Assessment Systems and practice. Semi-structured interviews, non-participant observations, and a literature review were used as data collection techniques to see what, how, when, who and why it is important to carry out assessment processes. The results were compared on the basis of theories defended by authors such as Porlán, Pozo, Morin, Tejada, Casanova, and Santos. It became evident that the roots of conceptions in teachers’ thinking bring with them heterogeneity in traditional assessment profiles that are considered in a reductionist way when operationalizing systems based on complexity.